2018
DOI: 10.3324/haematol.2018.192823
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 programs differentiating acute promyelocytic leukemia cells in all-trans retinoic acid treatment to inflammatory stage through NF-κB activation

Abstract: Differentiation syndrome (DS) is a life-threatening complication arising during retinoid treatment of acute promyelocytic leukemia (APL). Administration of all-trans retinoic acid leads to significant changes in gene expression, among the most induced of which is transglutaminase 2, which is not normally expressed in neutrophil granulocytes. To evaluate the pathophysiological function of transglutaminase 2 in the context of immunological function and disease outcomes, such as excessive superoxide anion, cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…In earlier studies, others tested a novel irreversible TG2 inhibitor NC9 to identify agents that can selectively target cancer stem cells in tumors [13,19,20]. Our studies demonstrated that elevated protein expression of TG2 could lead to inflammatory reactions [20,21].…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…In earlier studies, others tested a novel irreversible TG2 inhibitor NC9 to identify agents that can selectively target cancer stem cells in tumors [13,19,20]. Our studies demonstrated that elevated protein expression of TG2 could lead to inflammatory reactions [20,21].…”
mentioning
confidence: 89%
“…Endothelium damage with a capillary leak, edema, hypotension, fever, rash and dyspnea, pulmonary infiltrates, pleural or pericardial effusions and tissue infiltration may ensue [24]. In the last decade, dexamethasone or prednisolone prophylaxis has been used for the prevention of DS during the remission induction phase, but it is ineffective in reducing mortality developing from DS [25].We also previously demonstrated that shRNA-mediated knock-down or genomic deletion of TG2 in differentiating NB4 cell lines can decrease the levels of chemokines and cytokines, whose production is involved in the development of DS [20,23]. As a diminished expression of TG2 in differentiating APL cells may attenuate the ATRA-induced systemic inflammatory response syndrome…”
mentioning
confidence: 99%
See 3 more Smart Citations